Effectiveness of a training based on Guilford Evaluative Thinking Matrix, to examine its effect on the improvement of V-Shape evaluation strategy limitation and the improvement Science of teachers in teaching the activities and processes of the cell - Mahmoud rashed shdaifat (Journal of Educational Sciences, 2018)
This study aims at building a training program based on Guilford Evaluative Thinking Matrix, to examine its effect on the improvement of V-Shape evaluation strategy limitation and the improvement of teaching cell's activities and operations. The study was applied on 33 teachers and 666 students. The sample is separated into three groups: an experimental group for the program's effect, an experimental group for the V-Shape and a control group. To achieve the aim of the study a training program was designed to develop the teacher’s evaluation abilities based on Guilford Evaluative Thinking Matrix, a measurement tool was prepared for the teacher’s evaluation abilities consisted of 33 items and achievement test was prepared for the students and an achievement test is prepared depended on cell's activities and operations objectives. The results showed that there is an effect according to the program on treatment the teachers' evaluation limitation. To the students' achievement test, there was a significant difference for experimental group according to the program. But there was low effect in the science achievement test according to the program for the middle third students , the low effect was caused by teachers' low experience in using the program. There was no significant difference was caused by gender or the school type.